Advancement of Online Medical Consultation for Future - Abilash.L; Danushan.R; Agash.V; Abinaya.T; D.I.De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The internet has been a best source for the medical service previously, anyhow the internet has been using to maintain the best patient-doctor relationship. Applications offering healthcare services on the move have recently become more prevalent on the market. They have been the trending in worldwide. Our online medical consultation is secured for the users to login individually and to process their services. This study presents an analysis of the published surveys and reports as well as the literature on online medical consultation from different databases. According to published studies, reports, and surveys, there has been a dramatic increase in online medical consultations due to several causes, including convenience, changes in illness patterns, cost-effectiveness, privacy, and second opinions.